Pemanfaatan Internet Sebagai Sumber Pembelajaran Di Sd Negeri Pondok Ranji 02 - Ramadani, Putri; Maknun, Lu’luil (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
Abstract This research is a descriptive qualitative research that aims to reveal related to the use of the internet as a source of learning, which was conducted at SD NEGERI PONDOK RANJI 02. Data collection was carried out by conducting interviews, observations, and documents. Results from interviews, observations and documents were then analyzed using descriptive techniques. Data was collected using data triangulation, namely comparing observational data with interview data and with documents. The results of research on how to use the internet as a learning resource SD NEGERI PONDOK RANJI 02, Forms of using the internet as a source of learning SD NEGERI PONDOK RANJI 02 which is carried out by teachers and students is by assignment by the teacher, students are given the task of finding, learning, and expressing when learning to enrich the limited material in children's books and worksheets used during learning and to answer questions that arise during discussions, children's high desire to seek knowledge from various sources obtained through browsing and searching on the internet.